Enhancing Process Skills and Learning Outcomes: A Comparative Study of the Treffinger Learning Model - Mohammad Amin Lasaiba; Djamila Lasaiba (Journal of Innovative Science Education, 2023)
The Treffinger Model is an instructional approach developed with the primary goal of stimulating creativity and building process skills skills in students. This study aims to assess the extent to which the Treffinger Model enhances process skills abilities and student learning outcomes in addressing complex geographical challenges. A quantitative approach, specifically quasi-experimental design, was adopted to compare the effectiveness of the Treffinger Model with conventional teaching methods. The research involved two groups of eighth-grade students, with one group taught using the Treffinger Model and the other group through conventional methods. Data were collected for process skills and learning outcomes through pre-test and post-test assessments. The findings of this research indicate that the Treffinger Model has a significant positive impact on students' process skills and learning outcomes. The analysis of process skills reveals that students exposed to the Treffinger Model demonstrated improved abilities in observation, communication, grouping, measurement, drawing conclusions, and prediction. Additionally, the analysis of learning outcomes reveals that students taught with the Treffinger Model achieved higher average scores compared to those taught using conventional methods. The novelty of this research lies in its exploration of innovative pedagogical approaches and their impact on students' process skills abilities to comprehend and analyze geographical concepts more deeply. The benefit to the advancement of knowledge is the potential to increase students' interest and produce a generation of individuals who are more aware and knowledgeable about geographical issues.